1999
DOI: 10.2500/105065899781389696
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sinonasal Symptoms in Patients with HIV Infection

Abstract: Infection with the human immunodeficiency virus (HIV) is increasing in prevalence, and disease patterns are changing as patient survival lengthens. The purpose of this cross-sectional epidemiological study was to assess the prevalence and severity of self-reported symptoms of otolaryngologic disease in a group of patients attending a general HIV outpatient clinic (n = 203), and to compare the prevalence of self-reported symptoms with a sample of patients without HIV infection (n = 100). Of the HIV-infected pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 18 publications
1
22
1
2
Order By: Relevance
“…Prevalence of this disease in these individuals varied from 10% to 68%, as reported in the literature 1,2,4,5 .…”
Section: Introductionmentioning
confidence: 61%
See 4 more Smart Citations
“…Prevalence of this disease in these individuals varied from 10% to 68%, as reported in the literature 1,2,4,5 .…”
Section: Introductionmentioning
confidence: 61%
“…Porter et al 1 , when comparing seropositive patients -with or without AIDS -, also concluded that the symptoms and severity of rhinosinusitis were similar in both groups. However, we observed in our study that, from radiologically analyses, rhinosinusitis was more severe in AIDS patients, who presented extensive nasosinusal disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations